From institutionalized birth to home birth - Clara Fróes de Oliveira Sanfelice; Fernanda de Souza Freitas Abbud; Olívia Separavich Pregnolatto; Michelle Gonçalves da Silva; Antonieta Keiko Kakuda Shimo (Universidade Federal do Ceará, 2014)
The study aimed to describe the experiences of a group of nurse-midwives from the city of Campinas, SP, Brasil, regarding the transition process from attending institutionalized births to attending home births, in the period 2011 - 2013. The study is of the experience report type; the reflections, perceptions and challenges experienced in this process were collected using the technique of brainstorming. Content analysis, as proposed by Bardin, was used, which yielded four thematic categories: a) the hospital experience; b) living with obstetric violence; c) returning home and d) the challenges of home care. It is concluded that attending home births offers greater satisfaction to the nurses, even in the face of various obstacles, as it is possible to offer a care to the woman and new-born which covers both the concept of comprehensiveness and the current scientific recommendations.